Are Results in Geomorphology Reproducible?. Issue 8 (3rd August 2020) - Church, M.; Dudill, A.; Venditti, J. G.; Frey, P.
Abstract: There recently has arisen substantial concern for the reproducibility of scientific findings, but the discussion has not significantly impacted Earth science. We consider repetition, replication, and reproducibility in Earth science, using an example from geomorphology. Repetition repeats the program of observations in the same exercise to establish precision of results. Replication is duplication of observations using similar resources but in an independent program. Reproduction is confirmation of scientific principles using different resources in an independent program. We conclude that results will mainly be limited to reproduction—confirmation of principles—and that this is the essential goal for advancing the science. We illustrate these concepts by review of our experiments on the infiltration of fine grains in flowing water into a bed of coarser grains, conducted using glass beads in a laboratory flume. Plain Language Summary: Recent years have witnessed a rapid increase in concern for the confidence that can be placed in scientific results. The key to establishing such confidence is reproduction of the result under independent circumstances. The issue has been less discussed in Earth science than in other disciplines. In this commentary we draw attention to the issue using an example from geomorphology involving the infiltration of fine sediments in flowing water into a bed of coarser sediments. Key Points: The key feature of science—reproducibility of results—requires attention in the Earth sciences Key quantitative results require confirmation by replication General principles can be supported even by imperfect reproduction